Determination of Metabolizable Energy of Rich Unsaturated Fatty Acids Dry-Fat in Chicken Diets Using Chemical, Biological and Mathematical Methods - Selim , N.A.; Boulos, N.Z.; Abdel-Khalek, A.M.; Shabaan, M.; Radwan, N.L. (International Journal of Poultry Science, 2013)
Two biological experiments were conducted to determine apparent Metabolizable Energy (AME) of rich unsaturated fatty acids dry-fat (Polyfat® as an example, PF) using corn or corn-soybean meal diets with different inclusion levels of PF in adult cockerel diets. The biological experiments designed to follow procedures of excreta total collection method (TCM). The chemical evaluation of PF included determination of peroxide No., acid No., fatty acid profile and gross energy. Then different mathematical equations were applied to calculate AME of PF based on the chemical evaluation. The determined values of AME of PF using chemical methods were 7160 and 7188 kcal/kg for PF. Among biological experiments, using restricted quantity of corn diet with high levels of PF (25 or 50% of diet) resulted in lower AME values (4724 and 3992kcal/kg PF). While applying ad libitium consumption of corn-soybean practical diet containing 3% soybean oil (as reference oil), 3.8% of PF or 50:50 mixture of both (1.5% SO+1.9% PF), gave more realistic value of 6973 kcal/kg for PF. Mixing PF with soybean oil showed clear synergism effect and added caloric value of 9.6% (737 kcal) to the mixture above the expected value. Applying simple regression procedures on results of chemical and biological evaluations showed highly significant (p